Bridging the Tax-Expenditure Gap: Green Taxes and the Marginal Cost of Funds - Agnar Sandmo (Center for Economic Studies and ifo Institute (CESifo), 2001)
The marginal cost of public funds is usually seen as a number greater than one, reflecting the efficiency cost of distortionary taxes. But economic intuition suggests that since green taxes are efficiency-enhancing the MCF with such taxes will be less than one. The paper demonstrates that this intuition is not necessarily true, even when a green tax is the sole source of funds. The analysis also considers the MCF with a proportional income tax, given the presence of green taxes. It compares the optimization approach to the MCF with that of a balanced budget reform and shows that they lead to equivalent results.
Keywords: 330